A study of the dietary of college girls - Kratzinger, Elsie; Marty, Jessie (My University, 1908)
Introduction: This study and experiment extended through the month of April, 1908. The meals were prepared and served in one of the laboratories of Kedzie Hall. There were twelve girls that took part in the experiment, and also one of the instructors who had a general supervision of the work, and also acted as hostess at the table.
Citation: Kratzinger, Elsie and Marty, Jessie. A study of the dietary of college girls. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Diet; Nutrition; Food; Graduating theses; Senior theses; Theses